Impact of global social changes on the security of password authentication - Hub, Miloslav; Příhodová, Kateřina (Žilinská univerzita, 2018)
An authentication is the process of verifying the identity with the required degree of assurance. An example might be logging into e-mail inbox when a user firstly enters his username (identification) and his password (authentication). Although, different ways of authentication (biometrics, smart cards…) exist currently, an authentication through passwords is often used because of easy implementation and low financial requirements. But this way of authentication is not generally considered to be too secure because users often choose easy to guess short passwords, divulge theirs passwords to others, remark theirs passwords, and often use the same password for different services. Many existing passwords are not resilient to various forms of attack, such as a dictionary attack or brute force attack that also has relatively high economic impacts. However, due to globalization, there are significant social changes that affect the passwords that end users choose and therefore their security. At this time, users are choosing other passwords than they used to, such as choosing English terms for their passwords, using other mnemonic tools, and so on. The goal of this paper is to evaluate the password authentication security from the globalization point of view with respect to the ability of end users. Through the proposed dictionary attack and brute force simulation model, the attacks on the passwords that were acquired over the last fifteen years will be carried out and the impact of globalization on their security will be analysed.
Vliv sociálních změn na bezpečnost autentizace prostřednictvím hesel
Keywords: global social changes; security; authetication; passwords; dictionary attack; brute force attack